Decisões institucionais episódicas e seus reflexos na internacionalização de empresas de mercados emergentes - Halberstadt, Ismael Alan (2020)
The strategic decision-making process can be related to factors based on the industry, the specific resources of the company, or even use both together, added to the institutional conditions that the companies are immersed in. Peng (2008) presents a possible way for companies characteristic of emerging countries to use the strategy tripod (firm resources, specific company resources and institutional conditions / transitions) to formulate the strategies that these companies will use in environments of institutional uncertainties. As internationalization in emerging countries can be impacted by the strategic decisions that governments adopt, either to boost or to restrict international trade (CUERVO-CAZZURA et al., 2019), it sought to verify the reflex that the episodic decisions/actions of governments of an emerging country have had on the internationalization of companies in this context. Through the collection of secondary data and the construction of analysis categories, this dissertation used a longitudinal approach, with the Brazilian footwear sector as the focus of study, which presented episodic government decisions and reflected these in sometimes positive, sometimes negative ways. Data available at Comex-Stat, Abicalçados, UNCTAD, TIC, Statista and previous works that somehow addressed the sector and/or its internationalization were collected and analyzed. It is concluded that episodic decisions by federal government institutions, such as the opening of the market, implementation of the real plan, antidumping measures, exemption from payroll and labor reform reflected in the sector, even if some indirectly. The decisions of state governments were reflected in the relocation of industries in Brazil.